The heme oxygenase 1 product biliverdin interferes with hepatitis C virus replication by increasing antiviral interferon response - Lehmann, Elisabeth; El-Tantawy, Walid Hamdy; Ocker, Matthias; Bartenschlager, Ralf; Lohmann, Volker; Hashemolhosseini, Said; Tiegs, Gisa; Sass, Gabriele (Hepatology, 2010)
The anti-inflammatory and antiapoptotic heme degrading enzyme heme oxygenase-1 (HO-1) has been shown recently to interfere with replication of hepatitis C virus (HCV). We investigated the effect of HO-1 products carbon monoxide (CO), iron and biliverdin on HCV replication using the replicon cell lines Huh-5-15 and LucUbiNeo-ET, stably expressing HCV proteins NS3 through NS5B. Incubation of these cell lines in the presence of the CO donor methylene chloride transiently reduced HCV replication, whereas an increase of iron in cell culture by administration of FeCl3 or iron-saturated lactoferrin did not interfere with HCV replication. Likewise, depletion of iron by deferoxamine during induction of HO-1 by cobalt-protoporphyrin IX did not restore HCV replication. The most prominent effect was observed after incubation of replicon cell lines in the presence of biliverdin. Biliverdin seems to interfere with HCV replication-mediated oxidative stress by inducing expression of antiviral interferons, such as interferon alpha2 and alpha17. Conclusion: The antioxidant biliverdin reduces HCV replication in vitro by triggering the antiviral interferon response and might improve HCV therapy in the future. (HEPATOLOGY 2009.)
Gesehen am 13.03.2023